DJINNI: A Novel Technology Supported Exposure Therapy Paradigm for SAD Combining Virtual Reality and Augmented Reality - Ben-Moussa, Maher; Rubo, Marius; Debracque, Coralie; Lange, Wolf-Gero (Frontiers in Psychiatry, 2017)
The present paper explores the benefits and the capabilities of various emerging state-of-the-art interactive 3D and Internet of Things (IoT) technologies and investigates how these technologies can be exploited to develop a more effective technology supported exposure therapy solution for Social Anxiety Disorder (SAD). “DJINNI” is a conceptual design of an in-vivo Augmented Reality (AR) Exposure Therapy mobile support system that exploits several capturing technologies and integrates the patient’s state and situation by vision-based, audio-based and physiology-based analysis as well as by indoor/outdoor localisation techniques. DJINNI also comprises an innovative Virtual Reality Exposure Therapy system that is adaptive and customisable to the demands of the in-vivo experience and therapeutic progress. DJINNI follows a gamification approach where rewards and achievements are utilised to motivate the patient to progress in her/his treatment. The current paper reviews the state of the art of technologies needed for such a solution and recommends how these technologies could be integrated in the development of an individually tailored and yet feasible and effective AR/VR based Exposure Therapy. Finally, the paper outlines how DJINNI could be part of classical cognitive behavioural treatment and how to validate such a setup.